PEMANFAATAN HUKUM FARADAY UNTUK PEMBANGKITAN LISTRIK PADA SISTEM SUSPENSI KENDARAAN - Farzan, Affan Nabihan; Nugroho, Aditya Seto; Ramadhan, Mohammad Ikhsan; Sundana, Dimas Bagja Islami; Arbiansyah, Musa Barich; Winata, Achmad Rabbany Arsy; Irawan, Nanda (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2026)
A study has been conducted on the use of Faraday's electromotive force (EMF) to convert kinetic energy due to vibrations in vehicle suspensions into electrical energy through an electromagnetic induction-based Energy Harvester device. This device is mounted externally on suspension components, such as shock absorbers, so that the up-and-down movement of the suspension can be utilized without changing the characteristics or performance of the original suspension system. This study aims to identify the characteristics of the electrical output produced and emit potential induction mechanisms against vehicle suspension vibrations. This prototype device is designed with a permanent magnet configuration and coils that move relative to the dynamics of the suspension, then tested using variations in vibration amplitude and frequency. The measurement results show that the device produces an electrical signal with a voltage in the range of 0.06–0.11 V and a current in the range of 0.22–0.33 microamperes. These output values ​​are still below the minimum limit for powering simple loads, such as LEDs, or for detection by charging regulators. Analysis shows that the low output is influenced by the small magnetic field strength, the insufficient number of coil turns, the damping of the mechanical system, and the limited amplitude of suspension vibrations under test conditions. From the results of the research that has been conducted, it can be concluded that electrical energy can be generated from the vertical movement of the vehicle suspension. The amount of electrical energy generated is influenced by several factors, including the magnitude of the magnetic flux, the relatively low AC voltage and current values, the absence of energy storage components such as capacitors or supercapacitors, and the minimum operating voltage limit of the regulator. ABSTRAK Telah dilakukan penelitian mengenai pemanfaatan Hukum gaya gerak listrik (GGL) Faraday untuk mengkonversi energi kinetik akibat getaran pada suspensi kendaraan menjadi energi listrik melalui perangkat energy harvester berbasis induksi elektromagnetik. Perangkat ini dipasang secara eksternal pada komponen suspensi, seperti shock breaker, sehingga gerakan naik–turun suspensi dapat dimanfaatkan tanpa mengubah karakteristik atau kinerja sistem suspensi asli. Penelitian ini bertujuan mengidentifikasi karakteristik keluaran listrik yang dihasilkan serta mengevaluasi potensi mekanisme induksi terhadap getaran suspensi kendaraan. Perangkat prototipe ini dirancang dengan konfigurasi magnet permanen dan kumparan yang bergerak relatif mengikuti dinamika suspensi, kemudian diuji menggunakan variasi amplitudo dan frekuensi getaran. Hasil pengukuran menunjukkan bahwa perangkat menghasilkan sinyal listrik dengan tegangan pada kisaran 0,06–0,11 V dan arus pada kisaran 0,22-0,33 mikroampere. Nilai keluaran tersebut masih berada di bawah batas minimal untuk menyalakan beban sederhana, seperti LED, maupun untuk terdeteksi oleh regulator pengisian. Analisis menunjukkan bahwa rendahnya keluaran dipengaruhi oleh kecilnya kekuatan medan magnet, kurangnya jumlah lilitan kumparan, redaman mekanis sistem, dan terbatasnya amplitudo getaran suspensi pada kondisi pengujian. Dari hasil penelitian yang telah dilakukan, maka dapat disimpulkan bahwa energi listrik dapat dihasilkan dari gerakan vertikal suspensi kendaraan. Besar kecilnya energi listrik yang dihasilkan dipengaruhi oleh beberapa faktor, diantaranya adalah besarnya fluks magnet, nilai tegangan dan arus AC yang masih relatif kecil, ketiadaan komponen penyimpan energi seperti kapasitor atau superkapasitor, serta batas minimum tegangan kerja pada regulator.